Comparison of Electrocardiogram and QT Interval between Viral Hepatitis Cirrhosis and Alcoholic Cirrhosis - Li-Hong Lu; Xue-Ya Lv; Qi-Ming Wu; Qian Dong; Zhao Wang; Su-Juan Zhang; Li Fu; Qian Wang; Yu-Qing Song (Cardiology Research and Practice)
Objective. This study aims to compare the electrocardiogram (ECG) abnormalities and QT interval prolongation in 2,886 patients with viral hepatitis cirrhosis and 643 patients with alcoholic cirrhosis in order to understand the characteristics of ECG in patients with cirrhosis and provide information and evidence for clinical diagnosis and treatment. Methods. The ECG data of patients with viral hepatitis cirrhosis and alcoholic liver cirrhosis in the outpatients and inpatients of our hospital from August 2012 to July 2018 were reviewed. The ECG data were recorded, and the ECG report was issued by ECG experts to analyze the abnormal ECG and QT interval of patients in these two groups. Results. In the present study, 1,132 (39.22%) of the 2,886 patients with viral liver cirrhosis and 322 (50.08%) of the 643 patients with alcoholic liver cirrhosis had an abnormal ECG (P < 0.001). Among patients with QT prolongation, 388 patients had viral liver cirrhosis (13.44%) and 170 patients had alcoholic liver cirrhosis (26.44%, P < 0.001). Conclusion. The hemodynamics and electrophysiology of the myocardium are often changed in patients with cirrhosis, and ECG changes may also occur. QT interval prolongation is one of the most common electrophysiological abnormalities in patients with cirrhosis, and QT prolongation is more common in patients with alcoholic liver cirrhosis. Prolonged QT is associated with severe arrhythmia and sudden death and can warn of malignant arrhythmia and sudden death. Therefore, the routine detection of abnormal ECG and QT interval in patients with liver cirrhosis is of significant importance for preventing malignant events.